Gain‐flattened hybrid EDFA operating in C + L band with parallel pumping distribution technique. Issue 6 (1st December 2020) - Al‐Azzawi, Alabbas A.; Almukhtar, Aya A.; Dhar, Anirban; Paul, Mukul C.; Ahmad, Harith; Altuncu, Ahmet; Apsari, Retna; Harun, Sulaiman Wadi
Abstract : A novel C + L band hybrid erbium‐doped fibre amplifier (EDFA) using a two‐stage configuration was proposed and demonstrated experimentally. The amplifier is composed of a 0.5‐m long hafnium bismuth erbium co‐doped fibre (EDF) to provide gain within the C‐band and a 4‐m long zirconia‐based EDF to provide gain within the L‐band. The proposed amplifier was examined based on the multi‐wavelength input source. A parallel pumping distribution technique was used to mitigate the amplifier complexity. The C + L band amplifier achieved a gain flattening of over 55 nm bandwidth for the three levels of the input powers. A gain‐flattening of roughly 10.9, 15.5, and 19.2 dB were obtained, respectively, for the input signal powers of −5, −10, and −15 dBm. An average noise figure of 6.4, 5.4, and 4.7 dB was achieved, respectively, for the input signal powers of −5, −10, and −15 dBm.